The Impact of Land Fires on Soil Chemicals Propertiest (pH, Organic Carbon, Nitrogen, Phosphor, and Potassium) - imam khoirudin (Jurnal Agroekoteknologi Tropika Lembab, 2018)
This result aims to determine the impact of land fires on chemicals soil. Forest fire data Obtained in the region of Research and Edication Forest Bukit Soeharto Mulawarman University (HPPBS UNMUL). The method was used on research are descriptive and comparative by comparing the result of soil chemicals properties analysis of burn and unburned lands. The soil chemistry properties of this result is pH, Organic Carbon, Nitrogen, Phosphor and Potassium. Soil sampling was random system on this methods. Soil samples be distinguished by type and depth of soil sampling. The results of the soil analysis chemical properties then was compared based on assessment of soil chemical properties which refers to the assessment criteria soil chemical properties developed by Soil Research Institute Bogor, 2005. The results showed the fires occurring after 1 year influence of soil chemicals properties such as pH, Organic Carbon, Nitrogen, Phosphor and Potassium.